Magnesium and microminerals: roles, deficiency and excess - John Knight (Nursing Times, 2024)
Completing a six-part series, this article discusses magnesium and the key microminerals needed by the body in smaller amounts. Iron is essential for haemoglobin synthesis, and deficiency can lead to anaemia; iron-binding proteins can also deprive bacteria of iron, reducing infection. Copper, zinc and manganese all act as enzyme cofactors. Iodine is involved in regulating metabolism. Other microminerals are needed at extremely low concentrations; these ultra-trace elements include selenium, molybdenum, cobalt and chromium, all of which are discussed in terms of their role. Citation: Knight J et al (2024) Magnesium and microminerals: roles, deficiency and excess. Nursing Times [online]; 120:7.